Association of Hypothyroidism and Anti-Thyroid Antibodies With Preterm Delivery: A Cross Sectional Study - Tahereh Behroozi-Lak; Ameneh Akbary; Shabnam Vazifekhah; Mohammad Naghavi-Behzad; Mohammad Mirza-Agh (Tehran University of Medical Sciences, 2018)
Objective: Preterm delivery is a common and eventful phenomenon with long standing complications, heavily burdening the health system. Many risk factors have been suggested to increase the likelihood of this event, one being hypothyroidism and high levels of anti-thyroid antibodies. The present study sought to explore the association between hypothyroidism and anti-thyroid antibodies with preterm delivery. Materials and methods: A case control study was conducted on 400 patients attending Educational-Medical centers of Urmia University of Medical Sciences (Urmia, Iran) between November 2013 and April 2016, in which 200 patients with term deliveries and 200 patients with preterm deliveries were compared for differences in hypothyroidism, existence of anti- thyroperoxidase (TPO) antibodies based on blood samples obtained from the patients which were tested using chemi-luminescence method. Results: In the group of patients with preterm delivery, 85 patients had hypothyroidism (42.5%), and from the term delivery group, 67 patients (33.5%) had hypothyroidism, the difference was not statistically significant (p = 0.14). But, when groups of early and late preterm deliveries were compared in terms of having anti-TPO antibodies, there was a significant difference between them, with early preterm delivery having 8 patients positive out of 44 patients and late preterm delivery having 7 positives out of 141 patients (p = 0.004). Conclusion: Hypothyroidism had an insignificant effect on preterm delivery rates, but the existence of anti-TPO antibodies in the serum had a significant increasing effect on early preterm deliveries and could be regarded as a risk factor.